Evaluación de la concentración de leche y suero lácteo en la elaboración del manjar - Quishpe Chanatasig, Hilda Narcisa (2022)
This research aims to evaluate the concentrations of cow's milk and whey in the preparation of caramelized condensed milk to take advantage of the nutritional value and give added value to the whey. To define the different concentrations of cow's milk (90, 80, 70.50) and whey (10, 20, 30.50), a randomized complete block design (DBCA) was used with one factor, the ratio of milk and whey where the blocks are considered to each of the tasters. The fresh raw material was used to preserve the quality of the product, and the participation of twenty semi-trained tasters, whose obtained values were processed in the Infostat program to get the best treatment; through this procedure, treatment t1 turned out to be the best, which has a concentration of 90% milk and 10% whey. The caramelized condensed milk was subjected to physicochemical analysis, where the following results were obtained: humidity (heating loss) 15.49%, protein 6.06%, fat 9.06%; cholesterol 41.03mg/100g; total sugars 55.99%; ash 1.57%, sodium 16676.83 mg/kg; carbohydrates 67.28%, calories 377.06; does not contain crude fiber. The microbiological analysis corresponding to the mold and yeast count parameters results in <10 CFU/g, which guarantees that the caramelized condensed milk was prepared to obtain an innocuous product under hygiene and quality standards. In the nutritional analysis, there are 60 kcal, fat energy 15 kcal, total fat 1.5 g, saturated fatty acids 1 g; content of monounsaturated fatty acids, polyunsaturated fatty acids, and trans fatty acids is not detected, cholesterol 6mg, sodium 25mg, carbohydrates 10g, does not contain fiber, sugars 8g, Protein 1g, in such a way that this product provides the necessary nutrients for the human body; which must be ingested according to the energy balance of each person.